2023
DOI: 10.3390/jcm12093256
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: Low-Dose Ketamine for Pain Management

Abstract: Pain is the leading cause of medical consultations and occurs in 50–70% of emergency department visits. To date, several drugs have been used to manage pain. The clinical use of ketamine began in the 1960s and it immediately emerged as a manageable and safe drug for sedation and anesthesia. The analgesic properties of this drug were first reported shortly after its use; however, its psychomimetic effects have limited its use in emergency departments. Owing to the misuse and abuse of opioids in some countries w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 287 publications
0
3
0
Order By: Relevance
“…A study comparing an intravenous subdissociative dose of ketamine with morphine for analgesia in geriatric patients showed comparable analgesia with higher rates of psychoperceptual side effects [ 28 ]. A slower metabolism in elderly patients was discussed [ 29 ]. A study of low-dose esketamine for induction of anesthesia in elderly patients undergoing knee arthroplasty again showed no adverse events in the recovery period [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing an intravenous subdissociative dose of ketamine with morphine for analgesia in geriatric patients showed comparable analgesia with higher rates of psychoperceptual side effects [ 28 ]. A slower metabolism in elderly patients was discussed [ 29 ]. A study of low-dose esketamine for induction of anesthesia in elderly patients undergoing knee arthroplasty again showed no adverse events in the recovery period [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine inhibits glutamatergic neurons primarily through its antagonistic action on NMDA receptors. However, its action on dopaminergic, adrenergic, serotoninergic, opioid, and cholinergic receptors, as well as on spinal GABA interneurons, appears to be responsible for the analgesic effect of this drug, which is effective in chronic, neuropathic and cancer pain [ 99 ]. In addition, corticosteroids, and magnesium sulphate [ 100 , 101 , 102 ] have been shown to be useful adjuvants, especially in neuropathic pain and bone pain [ 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial treatment consists of reducing or eliminating the current opioid dose or switching to an opioid with less neurotoxic effects, such as fentanyl, and maximising non-opioid adjuvants when indicated. The use of low-dose ketamine for pain relief may have a role in the management of this issue in the ED [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine administered at three different doses (0.15 mg/kg, 0.30 mg/kg, and 0.45 mg/kg) during the performance of the procedures has been shown to decrease patient response, facilitate lumbar puncture, and improve hemodynamic parameters [6]. The side effects of ketamine include hypertension, nausea, agitation, confusion, and hallucinations, although these are dose-dependent and are extremely rare at low doses [8][9][10]. It was observed that the undesirable side effects of ketamine increased at doses of 0.45 mg/kg and above [6].…”
Section: Introductionmentioning
confidence: 99%